1991
DOI: 10.1109/32.83915
|View full text |Cite
|
Sign up to set email alerts
|

An information retrieval approach for automatically constructing software libraries

Abstract: Although software reuse presents clear advantages for programmer productivit.y and code reliability, it is not practiced enough. One of the reasons for the only moderate success of reuse is the lack of software libr'lries that facilitate the actual locating and understanding of reusable components. This paper dpscrihes II technology for automatically I\Ssembling large softwar~ libraries that promote softwarp rpuse by helping the user locate the components closest to hfO'r/his neeels Softwarp libraries are aut.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
196
0
2

Year Published

1995
1995
2003
2003

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 367 publications
(198 citation statements)
references
References 25 publications
0
196
0
2
Order By: Relevance
“…The retrieval mechanism of CodeBroker is similar to that of those systems using free-text indexing [12]. Many sophisticated retrieval mechanisms have been proposed, such as multifaceted classification, frames and semantic networks, and associative networks [13].…”
Section: Related Workmentioning
confidence: 99%
“…The retrieval mechanism of CodeBroker is similar to that of those systems using free-text indexing [12]. Many sophisticated retrieval mechanisms have been proposed, such as multifaceted classification, frames and semantic networks, and associative networks [13].…”
Section: Related Workmentioning
confidence: 99%
“…For instance, we could use vocabulary normalization tools such as synonym list and thesarus associations, or using adjacent words to form term-phrases (Maarek et al, 1991;Chen et al, 1994). We have to emphasize, however, that it has been often reported that in many practical situations the use of more elaborated systems than single-word term extraction did not result in significant performance improvement (Salton, 1989).…”
Section: Word Weightingmentioning
confidence: 99%
“…However, the statistical clustering methods that have predominately been used in information retrieval (e.g., Willet, 1988;Crouch et al, 1989;Maarek et al, 1991) are affected by their inability of producing a conceptual description of the classes generated. By contrast, conceptual clustering techniques usually provide an intensional description of the clusters generated, which may improve both the effectiveness of hierarchy navigation, for interactive searches, and the efficiency of the query-cluster matching process, for automatic searches.…”
Section: Concept Lattices As Retrieval Support Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Only a few prototype tools have been developed to aid matching of requirements (Maarek et al, 1991;Maiden and Sutcliffe, 1991;Cybulski, 2001). Some related tools can help, however.…”
mentioning
confidence: 99%